How to write and give a speech a practical guide for executive, PR people, managers, fundraisers pliticians, educators, and anyone who has to make every word count. - Detz, Joan (St. Martin's Press, 1984)
Contents: Common difficulties of businessmen and professionals in public speaking. Planning ideas. Work with words. Connect with the audience. Manage your visuals. Business presentations. Special concerns. Sample speeches. Index.